Numerical simulation of transient moisture transport for hygroscopic inertia assessment - V. P. Freitas (2012)
The finishing layers of walls and ceiling may be important contributors to a room's hygroscopic inertia and therefore reduce peak values of relative humidity variation. The precise hygric simulation of the surface layers can be important for improving the design of these building elements. This paper reports the results from systematic simulation of a set of dynamic experiments of transient moisture transfer in the hygroscopic region using HAM-Tools software. The authors use a set of laboratory experiments to verify and correct the modelling assumptions and the basic data used in simulations, to select the most effective strategies for conducting this type of simulation. Previous standard measurements of sorption isotherms and vapor permeability for gypsum-based revetments and applied coatings provided basic material data for numerical simulations. Two types of simulations of actual laboratory tests were then performed: (7) Moisture Buffer Value (MBV) tests for validation of material modelling and (2)flux chamber tests for validation of room air and material coupling. As a means of bringing these concepts closer to practice, the generalization of a daily hygroscopic inertia index application in a simple assessment method is improved and supported by the latter simulations.